GAMBARAN PENERAPAN DISIPLIN PROTOKOL KESEHATAN SELAMA NEW NORMAL DI MI NURUL HUDA PANGENAN - liajamaliyah liyah; Puja lestari; Jahid sabilal khoir; Afiyatun kholifah (Al Naqdu, 2022)
Many cases of Covid-19 were found in workers, including teachers. Currently, many schools have been opened, therefore the implementation of health protocols in schools must be considered and good behavior towards health protocols is always maintained. The purpose of this study is to describe the behavior of the workforce and the implementation of the health protocol discipline program during the Covid-19 pandemic at MI NURUL HUDA PANGENAN. This study uses a qualitative method with research informants consisting of 4 informants selected based on the suitability and adequacy of the data. The key informant consisted of one person, namely the principal, then for the core informant there were 3 people, namely 2 teachers and one janitor. The variables contained in this study were knowledge, attitudes, sanitation and hygiene facilities, availability of PPE, health protocol policies, and application of health protocols in schools. The results obtained are that most of them have good knowledge and also have a positive attitude, the availability of sanitation and hygiene facilities is adequate, but for PPE, namely masks are not yet available, then the absence of written policies affects the application of health protocols so that the implementation of health protocols is based on policies in education units. it's enough but it can't be said to be very good but the behavior of implementing the health protocol for the workforce has been good.